2020
DOI: 10.1186/s10020-020-00199-7
|View full text |Cite
|
Sign up to set email alerts
|

Serum a proliferation-inducing ligand and MicroRNA-223 are associated with rheumatoid arthritis: diagnostic and prognostic implications

Abstract: Background Current blood-based tests for rheumatoid arthritis (RA) have inherent limitations, necessitating the need for additional new biomarkers for its diagnosis and monitoring disease activity and responsiveness to therapy. MicroRNAs (miRNAs) and a proliferation-inducing ligand (APRIL) are deregulated in RA and were linked to its pathogenesis. This study investigated serum levels of APRIL, miR-223 and miR-155 in RA patients, their potential as diagnostic and prognostic biomarkers, and their correlation wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“… 233 In addition, patients with established rather than early RA exhibited higher expression of serum miR-223 than unaffected controls. 234 , 235 A study by Ouboussad et al suggested a pronounced increase in the expression levels of serum miR-22 after progression from the preclinical state to early RA. Serum miR-22 is therefore deemed an important predictor of the onset and development of RA.…”
Section: Mirna-based Diagnostic Strategies For Ramentioning
confidence: 99%
See 1 more Smart Citation
“… 233 In addition, patients with established rather than early RA exhibited higher expression of serum miR-223 than unaffected controls. 234 , 235 A study by Ouboussad et al suggested a pronounced increase in the expression levels of serum miR-22 after progression from the preclinical state to early RA. Serum miR-22 is therefore deemed an important predictor of the onset and development of RA.…”
Section: Mirna-based Diagnostic Strategies For Ramentioning
confidence: 99%
“… 235 , 244 Taha et al later proposed the conflicting view that serum miR-155 expression does not differ between RA patients and controls. 234 Overall, the intrinsic and extrinsic factors affecting circulating miRNA levels have not been fully characterized. The sex, age, race, and lifestyle of the subjects, techniques employed for miRNA analysis, study design and stage of disease may all contribute to the differences in circulating miRNA signatures.…”
Section: Mirna-based Diagnostic Strategies For Ramentioning
confidence: 99%
“…Rheumatoid arthritis (RA) is a chronic inflammatory disease. Studies have demonstrated that miR-223 is significantly higher in the plasma, serum and peripheral mononuclear cells (PBMCs) of RA patients than those of controls, indicating that miR-223 could be associated with the development, progression and severity of RA 92 , 93 . The reliability of the biological functions of miR-223 in RA has been confirmed by accurately measuring the AUC value, and sensitivity and specificity of miR-223 94 .…”
Section: Role Of Mir-223 In Inflammatory Diseasesmentioning
confidence: 99%
“…Moreover, expression profile of miRNAs is variable and depends on diseases entities [ 106 ]. In the case of RA many studies revealed correlation between different clinical parameters and dysregulation of expression analyzed miRNAs [ 41 , 107 , 108 ]. Many studies show that level of microRNA may help to predict therapeutic effects [ 70 , 109 , 110 , 111 , 112 ].…”
Section: Micrornamentioning
confidence: 99%